SARKASME DALAM CERPEN “MALAM SEORANG MALING” KARYA JAKOB SUMARDJO (SEBUAH KAJIAN SEMANTIK) - -, Haniyah (Jurnal Bahasa Indonesia Prima (BIP), 2023)
Some people use sarcasm to express anger, annoyance, etc. This research aims to examine the form of sarcasm in the short story Malam Seorang Maling by Jakob Sumardjo, end the form of sarcasm in the 70s. The research method used in this research is the descriptive qualitative method. The content analysis technique is used by recording the findings. From the analysis that has been done, 10 sarcasm data were found. Based on the findings, the target of sarcasm is only sometimes addressed to living objects, such as human being or their group, but to non-living objects, such as suitcases and hallways.